Preconceito e discriminação étnico-racial no ambiente escolar: dilemas diariamente enfrentados pelos profissionais da educação - SILVA, Marcia Cristina da (2020)
This article discusses prejudice, and ethnic-racial discrimination in the school environment, aiming to understand how schools and their teachers prepare to face discrimination in the classroom in elementary school. We seek to understand the discriminatory roots historically in order to glimpse how ethnic racial prejudice has developed in society and its reflections in school, as well as the physical and psychological consequences for those who suffer this type of violence. We also reflect on Law 10.639 and the main difficulties faced by teachers in their implementation, in accordance with the National Curricular Guidelines for the Education of Ethnic-Racial Relations in Education and for the Teaching of Afro-Brazilian and African History and Culture. How to adjust the curriculum through these racial inequalities?